Prevalence and Associated Factors of Low Birth Weight in Central Sudan: A Cross-sectional Study - Nagat B. Elhag; Hager M. Alabass; Omaima A. Hamid; Khalid Albasheer; Ishag Adam (Sudan Journal of Medical Sciences)
Background: This study aims to assess the prevalence and associated factors of low birth weight (LBW) in central Sudan during the ongoing instability.